Linseed as new host for emerging pathogens dichotomized through molecular phylogeny from Karnataka, India: Linseed as new host for emerging pathogens dichotomized through molecular phylogeny from Karnataka, India - K AJITHKUMAR; A S SAVITHA; S MAHADEVAKUMAR; S S N MAHARACHCHIKUMBURA; M Y SREENIVASA; A L RATHNAKUMAR; M SUJATHA (Journal of Oilseeds Research, 2023)
A characteristic disease was noticed in linseed with symptoms that resembled phytoplasma disease with 6·5 to 16·5 per cent incidence at UAS, Raichur. Previously linseed is known to be associated with 16SrII-D phytoplasma but the association of the 16SrXIV-A group of phytoplasma is the new host record for Ca. P. cynodontis (16SrXIV-A) phytoplasma associated with linseed stem fasciation, phyllody from India. A characteristic powdery mildew symptom with white fungal mycelial growth was noticed on the abaxial as well as on adaxial leaf surfaces. For molecular confirmation through ITS-rDNA barcoding, genomic DNA was amplified using powdery mildew-specific ITS universal primer pair PN23/PN34 and sequenced directly. The ITS regions were amplified at ~700bp and nBLAST analysis revealed that the ITS sequence shared 100 per cent similarity with reference sequence AB045148.1 respectively. Further amplification of L1/L2 primer pair from ITS region were PCR amplified and an expected amplicon of 374bp was analyzed. Though, the ITS-rDNA and L1/L2 specific region analyzed, they are not specific exclusively to the L. taurica. However, combination of morphology and molecular sequence was used to confirm the identity.